Saksenaea vasiformis: a multifaceted approach to a complex case - Hanna, Jessica E.; Bai, Michael; Carmichael, Gavin J.; Kidd, Sarah E.; Warner, Morgyn S.; Jog, Shivangi (International Surgery Journal, 2025)
Saksenaea vasiformis is a rare, opportunistic Mucorales fungus capable of causing rapidly progressive cutaneous and subcutaneous infections, including necrotising fasciitis. Early diagnosis is challenging due to its poor sporulation on routine media and often subtle initial clinical features. We describe a case of a soft-tissue infection in a co-morbid 75-year-old man from rural Australia with limited healthcare engagement. Despite broad-spectrum antibacterial therapy, operative intervention and negative-pressure wound-therapy, the wound continued to deteriorate. Eventually, sequencing of the internal transcribed spacer region confirmed S. vasiformis. The patient was commenced on liposomal amphotericin B followed by prolonged oral itraconazole due to underlying renal impairment and geographic barriers to ongoing inpatient care. This case underscores the need for early suspicion of atypical fungal pathogens in necrotic soft-tissue infections unresponsive to antibacterial therapy and highlights the importance of prompt surgical management, infectious diseases input, specialised fungal diagnostics and tailored antifungal treatment.